2012
DOI: 10.1002/jmv.23423
|View full text |Cite
|
Sign up to set email alerts
|

Performances of four fourth‐generation human immunodeficiency virus‐1 screening assays

Abstract: Fourth-generation human immunodeficiency virus-1 (HIV-1) screening assays have improved sensitivity, but vary in performance characteristics. The purpose of this study was to evaluate four different fourth-generation HIV-1 assays. These assays included the AxSYM HIV Ag/Ab Combo (Abbott diagnostics, Delkenheim, Germany), ARCHITECT HIV Ag/Ab Combo (Abbott), Elecsys 2010 HIV Combi (Roche Diagnostics GmbH, Mannheim, Germany), and Elecsys HIV Combi PT (Roche). A total of 1,306 samples that included 1,225 clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…In current diagnostic algorithms, the fourth‐generation assays are implemented worldwide as an initial test. Nevertheless, multiple studies indicated that test performance may vary significantly in different demographic factors and geographic regions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In current diagnostic algorithms, the fourth‐generation assays are implemented worldwide as an initial test. Nevertheless, multiple studies indicated that test performance may vary significantly in different demographic factors and geographic regions …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, multiple studies indicated that test performance may vary significantly in different demographic factors and geographic regions. 11,12 As understanding the performance of fourth-generation assay in local region is pivotal to interpret the test result correctly, in the present study, we set out to analyze the Elecsys ® HIV combi PT assay in Shaocong Liang and Guihua Deng contributed equally our hospital with a situation of low HIV prevalence. The Elecsys ® HIV combi PT assay had been used in our laboratory for more than 2 years, some problems emerged during the testing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Newer fourth-generation HIV assays should be validated for the known limitation of previous assays. According to the recent studies [16, 17], the average specificity of the fourth-generation assay was from 99.5% to 99.9%, which was equivalent to that of the third-generation assays.…”
Section: Discussionmentioning
confidence: 97%
“…The p24 antigen, CHIV, and other combo assays should meet the analytical sensitivity at least 2 IU/mL using WHO standard, for approval of HIV combo assays in the Conformite Europeenne [22]. The newer fourth-generation HIV assays showed 1.13 IU/mL of lowest detection limit using HIV p24 antigen sensitivity panel [17]. Although we could not evaluate the analytical sensitivity of the ADVIA Centaur CHIV assay in this study, we may expect that it has the comparable sensitivity with other fourth-generation HIV assays.…”
Section: Discussionmentioning
confidence: 99%
“…Samples with signal to cut-off (S/CO) values greater than or equal to 1.0 are considered reactive and samples with S/CO values less than 1.0 are considered nonreactive. ARCHITECT HIV Ag/Ab Combo has high analytical sensitivities (sensibility 100%, specificity 99.6%) and would be preferable for reducing the window period [2].…”
mentioning
confidence: 99%